Investigation of hepatocyte growth factor and proinflammatory cytokine levels in patients with febrile neutropenia - Ozden, Mehmet; Godekmerdan, Ahmet; Ilhan, Nafiye Fulya; Elkiran, Emin Tamer; Akbulut, Hatice Handan (Tubitak Scientific & Technological Research Council Turkey, 2013)
Aim: It has been thought that hepatocyte growth factor (HGF) levels increase during acute phases of infectious diseases. The aim of this study was to determine whether HGF, C-reactive protein (CRP), and proinflammatory cytokines have any diagnostic and prognostic value, and to assess HGF as a biomarker in patients with febrile neutropenia. Materials and methods: This study included 20 patients with febrile neutropenia as the study group and 20 healthy individuals as the control group. Serial measurements of serum HGF, CRP, and proinflammatory cytokine levels were performed by enzyme-linked immunosorbent assay (ELISA) at the baseline, after 48 h of treatment, and at posttreatment. Results: It was found that HGF levels at the baseline were significantly higher than those in the healthy controls (P = 0.001). It was also seen that HGF levels 48 h after treatment and at posttreatment were significantly lower than those at the baseline (P = 0.012). High-risk group patients had higher mean serum HGF levels compared with the low-risk group. It was detected that IL-6 and TNF-alpha levels at the baseline were significantly decreased after treatment (P = 0.02 and P = 0.005). Conclusion: Our findings suggested that serial measurement of serum HGF levels may be an important marker to identify risk levels of febrile neutropenia and to predict its prognosis.
Keywords: Febrile neutropenia; hepatocyte growth factor; CRP; cytokine